In Absentia Data Bahasa dalam Kejahatan Berbahasa Putusan Mahkamah Agung: Kajian Linguistik Forensik - Hidayat, Rahmat; Arimi, Sailal (MIMESIS, 2024)
Violation of language norms committed by an individual can result in sanctions or punishment. The penalties imposed in cases of hate speech may include fines or imprisonment. In the case of Bahar bin Smith and Yulianus Paonganan, there were language violations, particularly in the form of insults, defamation, and tarnishing the reputation of President Joko Widodo. Bahar bin Smith was sentenced to six months and fifteen days, while Yulianus Paonganan was sentenced to one year of imprisonment. Interestingly, in the Supreme Court’s decision regarding Bahar bin Smith’s case, there is no information regarding language violations. This raises questions about how a punishment for language-related crimes can be decided without linguistic evidence. This research is descriptive and qualitative, using a semantic approach to identify forms of hate speech. The linguistic forensic research results highlight the forms, types, and grammatical meanings of hate speech. Furthermore, the research findings indicate that the Supreme Court, in issuing decisions, is not always professional, lacks transparency, and exhibits negligence and carelessness, as evidenced by the issuance of a verdict without linguistic violation evidence.